Farelo desengordurado de arroz e iodeto de potássio como fatores de retardamento da maturidade sexual de frangas - de Almeida e Silva, Martinho; Campos, Joaquim; da Silva, Dirceu Jorge; Soares, Paulo Rubens; Mayrose, Vernon (Revista Ceres, 2025)
The purpose ofthis experiment was to study the effects of different levels of defatted rice bran and the addition of iodine to a corn and soybean meal ration on growing pullets. This experiment consisted of two periods.